Analisis Efektivitas Program Zakat Produktif Dalam Menanggulangi Kemiskinan (Studi Kasus Di Badan Amil Zakat Nasional Kab. Asahan) - Raihan, An Nisa’u; Anggraini, Tuti; Harahap, M. Ikhsan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This study examines the issue of how to analyze the effectiveness of Baznaz’s effective zakat program in Kab. Asahan in the fight against poverty. The use of zakat in the Kab. Asahan Baznaz encountered a number of obstacles. The aimof this study is to obtain an analysis of what BAZNAS should do to address the existing problems in the management of zakat production to overcome poverty through qualitative methods, especially to overcome poverty. This study uses a descriptive method with qualitative research because it is of the type of qualitative descriptive research, wherein this research describes or describes research circumstances or conditions in detail and expertise. deep. The data collection techniques used in this study were observation, interview, and documentation. Theresult of this study was an analysis of the effectiveness of the zakat program in reducing poverty, the absence of intensive support and the limited knowledge and management of human resources, as well as the lack of have goals in distributing zakat efficiently. While the effectiveness of zakat produced in the Kab. Asahan Baznaz does not contribute significantly or is not effective for poverty reduction.